Desafíos del Derecho de la Competencia Ecuatoriano, luego del Examen Inter-pares de la OCDE y el BID - Pérez Ordóñez, Diego (2023)
The Peer Review assessment by the Organization for Economic Co-operation and Development, in collaboration with the Inter-American Development Bank, was a valuable effort to submit the Ecuadorian competition regime to a multilateral peer review. The evaluation revealed opportunities for improvement which constitute relevant challenges to develop the Ecuadorian competition law and policy.We will analyze some of the main findings. We will begin with an explanation of the constitutional basis of the Ecuadorian competition regime. Then, we will review the Report regarding the institutional bodies. We will present a state-of-the-art of enforcement function and judicial review. Subsequently, we will analyze the main comments regarding merger control. Finally, we state conclusions.